An active direct down conversion mixer for WLAN applications - Salmeh, R.; Maundy, B.; Johnston, R. (2004 1st International Conference on Electrical and Electronics Engineering : (ICEEE) : Acapulco, Mexico, 8-10 September, 2004, 2004)
The mixer is one of the fundamental circuit blocks of any wireless communication system. Most portable communication systems have at least two mixers, one in the receiver and another in the transmitter. Although high performance bipolar and CMOS mixers have been available for some time, their implementation is still a challenging subject for high frequency, Iow-voltage and low-power circuit design. In this paper an active direct down conversion mixer using a 47 GHz, SiGe, BiCMOS MMIC technology is presented. The mixer functions at 5 GHz and draws only 10.2 mW from a 3 V supply. The mixer has input LO and RF return losses of -26dB and -2SdB respectively. The overall conversion gain of the circuit is 8.5 dB.